Evaluating population structure of Ecuador for forensic STR markers. (December 2022) - Flores-Espinoza, R.; Angulo-Pozo, A.N.; Garzón-Salazar, A.; Cabrera-Andrade, A.; Paz-Cruz, E.; Burgos, G.; Gusmão, L.
Abstract: The continuous admixture events among Europeans, Native Americans, and Africans occurred differently throughout the Ecuadorian territory, creating a diversified genetic composition. Therefore, to evaluate how the genetic diversity is partitioned along the country for 15 STRs, 842 admixed-population samples were analyzed. We also evaluated the effect of applying an adjustment for population structure when estimating LRs using a national database. The results showed that to accurately assess forensic evidence, the use of a national database may be justified with the application of an appropriate adjustment for population structure.